Role of Toluidine Blue Staining in Suspicious Lesions of Oral Cavity and Oropharynx - Vijayakumar, Vidhu (Indian J Otolaryngol Head Neck Surg, 2017)
Oral cancer; the sixth most common malignancy in the world has one of the lowest 5 year survival rates. This can be attributed mainly to the delay in diagnosis. The purpose of this study was to evaluate the efficacy of vital staining with toluidine blue dye as an adjunct to standard clinical examination to facilitate early detection of malignant lesions of oral cavity and oropharynx. A hospital based diagnostic test accuracy study was carried out on 55 subjects with oral mucosal disorders that included clinically suspicious premalignant or malignant lesions, in the Department of ENT, Academy of Medical Sciences, Pariyaram, Kannur, Kerala over a period of 2 years. All lesions were subjected to detailed clinical examination and toluidine blue staining; and dye retention was recorded with photographs. The results of staining were compared with findings on histopathological examination. The Sensitivity and specificity of toluidine blue test for the detection of malignancy was 92.6 and 67.9% respectively; and the overall diagnostic accuracy was 80%. The result was highly significant with a ‘p value’ <0.001. The results indicate that toluidine blue staining is a simple, non-invasive technique which can be a valuable adjunct in the diagnostic process of oral and oropharyngeal cancers.